1974
DOI: 10.1104/pp.53.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Phloem Exudation from Cut Petioles by Chelating Agents

Abstract: The photosynthetic assimilates in leaves of Perilla crispa attached to the plant were labeled by treating the leaves with 4C02. When subsequently detached, these leaves exuded a negligible amount of radioactivity from the cut petiole into water. Ethylenediaminetetraacetate (EDTA), citric acid, and ethyleneglycol-bis(f8-aminoethyl ether) N,N'-tetraacetate greatly increased exudation of labeled assimilates into a solution bathing the petioles. The optimal concentration of EDTA was 20 mM, and maximal exudation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
301
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(308 citation statements)
references
References 18 publications
5
301
0
2
Order By: Relevance
“…Plants also deposit callose in sieve elements penetrated by stylets, thereby preventing the prolonged feeding of phloem-feeding insects. In plants, callose synthesis is Ca 2+ -dependent (King and Zeevaart, 1974). It has been shown that sieve tube occlusion upon wounding in legumes involves the dispersion of spindle like proteins (forisomes) with the aid of Ca 2+ influx to the injury site (Knoblauch et al, 2001;Thorpe et al, 2010).…”
Section: Defense In the Phloemmentioning
confidence: 99%
“…Plants also deposit callose in sieve elements penetrated by stylets, thereby preventing the prolonged feeding of phloem-feeding insects. In plants, callose synthesis is Ca 2+ -dependent (King and Zeevaart, 1974). It has been shown that sieve tube occlusion upon wounding in legumes involves the dispersion of spindle like proteins (forisomes) with the aid of Ca 2+ influx to the injury site (Knoblauch et al, 2001;Thorpe et al, 2010).…”
Section: Defense In the Phloemmentioning
confidence: 99%
“…Phloem sap was obtained by EDTA-facilitated exudation (King and Zeevaart, 1974). Four-to 6-week-old plants were grown in a greenhouse (16-h photoperiod).…”
Section: Phloem Sap Exudationmentioning
confidence: 99%
“…Phloem sap was obtained from mature rosette leaves with an EDTA-facilitated exudation technique (King and Zeevaart, 1974) adapted for Arabidopsis. The quality of the sap was confirmed by the smaller proportions of Glc and hexose than of Suc ( Fig.…”
Section: Pp2-a1-his 6 Binds To Phloem Sap Proteinsmentioning
confidence: 99%
“…Phloem exudates were collected from plants grown in the same conditions without aphids according to a protocol adapted from King and Zeevaart (1974) that allows the collection of phloem exudates without major contaminations. The petioles of 10 g of V. faba freshly cut leaves were placed in 20 ml of a 20 mM Na 2 EDTA solution for 1 h in the dark under 90% of relative humidity.…”
Section: Collection Of Phloem Exudatesmentioning
confidence: 99%